Ergonomic Analysis of Welding Postures on Productivity and Weld Quality Using the REBA Method - Danil Arifin, Mohammad; Yoseph Arya Dewanto; Aldyn Clinton Partahi Oloan; Kalpika Arhan Nugraha (International Journal of Marine Engineering Innovation and Research, 2025)
Ergonomics in the workplace plays a vital role in reducing the risk of musculoskeletal disorders, preventing accidents, and improving both work efficiency and productivity. In shipbuilding welding activities, workers are frequently exposed to awkward and static postures that lead to fatigue, stress, and long-term injuries, which may compromise weld quality and project performance. This study aims to analyze ergonomic risks across four welding postures i.e., downhand, vertical, horizontal, and overhead, using the Rapid Entire Body Assessment (REBA) and Nordic Body Map (NBM) methods. The REBA assessment indicated that downhand welding scored 10 (high risk), vertical welding 11 (very high risk), horizontal welding 8 (high risk), and overhead welding 9 (high risk). NBM results revealed that 77.5% of welders in vertical welding reported waist pain, 72.5% calf pain, and 70% back pain; horizontal welding showed 67.5% right-hand pain and 65% right-wrist pain; overhead welding resulted in 57.5% neck and waist pain; while downhand welding still caused 70% complaints in the back and calves. These findings confirm that welding ergonomics directly affect worker health, weld quality, and productivity. The study recommends ergonomic interventions such as scaffolding, adjustable supports, arm rests, and proper work rotation to minimize strain, enhance safety, and ensure efficiency in shipyard operations.